A young man with familial adenomatous polyposis coli: a case report - Jaafar, Khairul Azhar; Bunn, Andrea (Faculty of Medicine, International Islamic University Malaysia, 2007)
Familial adenomatous polyposis ( FAP ) accounts for about 1% of colorectal cases in the United States. FAP arises from the germline mutation of the adenomatous polyposis coli ( APC) gene located on chromosome 5Q21.In one third of cases it arises from spontaneous mutation and have no associated family history. As these polyps will progress to carcinoma the treatment of choice is total colectomy. This report describes a patient with a positive family history of carcinoma of the colon who developed rectal bleeding and was subsequently diagnosed as FAP following a colonoscopy.